The Quran and Muslim Minority Scholar’s Perspective: A Comparative Study of Abdullah Saeed and Farid Esack - Muhammad, Wildan Imaduddin; Rahman, Yusuf (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2022)
This article discusses an alternative perspective in understanding the content of the Qur’an i.e., the perspective of minority Muslim scholars. The object of this study is the thought of tafsir Abdullah Saeed and Farid Esack who are positioned as Muslim scholars of Western institutions living as a minority, how their views of the Qur’an and how they develop interpretive methodologies according to the context of the environment in which they live. This article shows that the construction of the thought of Abdullah Saeed and Farid Esack positioned as minority scholars can represent its own contemporary model of interpretation. Abdullah Saeed with the idea of contextual interpretation laid out three bases of interpretive methodology: hierarchical values, contextual meaning, and systematic contextual interpretation. The three bases of the methodology are used to see the extent to which verses on ethical law can be understood and practiced in contemporary contexts while remaining grounded in the substance of the values carried when they are derived. While Farid Esack with his idea of liberative exegesis tried to break conservatism in South Africa with three methodological foundations: progressive revelation, reception hermeneutics, and the liberation theology of the Qur’an. The foundation of this methodology was used as a basis for value and legitimacy in supporting the agenda of popular solidarity between Muslims and non-Muslims in South Africa to overthrow the apartheid regime.